Pengembangan CAI-kontekstual untuk meningkatkan kemampuan berpikir matematik dan karakter mahasiswa - Nanang Nanang (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2016)
This research was the development of mathematical learning model to improve students’ mathematical thinking and characters. The model developed was Computer Assisted Instruction (CAI) – Contextual in the course of mathematics capita selecta of high school. The research used research and development method through ‘thought experiments’ and ‘instruction experiments’ with a cyclical process. Subjects in this study were students of mathematics teacher education of STKIP Garut, consisted of three classes. The instruments developed were documentation study, interview guides for students, mathematical thinking ability tests and questionnaires to measure the student’s character. Based on the results achieved, it can be concluded: (1) There were a potential and opportunities that exist in the field to develop the components of CAI-Contextual, (2) CAI-Contextual potentials to improve students’ mathematical thinking and characters, and (3) Students’ mathematical thinking and characters increases on the average and the students have a good character.